Visit of a PTTI-delegation to the Philipines. Place of persons indicated on the back. Series of 2 photos of banquet offered by CWA to PTTI-oficials
Visit of a PTTI-delegation to the Philipines. Place of persons indicated on the back. Series of 2 photos of banquet offered by CWA to PTTI-oficials.